Human governance and firm success from western and Islamic perspectives - Noraina Mazuin, Sapuan; Norwazli, Abdul Wahab; Mahfud, Sholihin; Intan Syazwanie, Sawaluddin (Penerbit Universiti Malaysia Pahang, 2020)
Human governance is an essential internal value that acts as a guide for a human to behave. Positive internal values can be the drivers to inspire people to work with integrity and accountability for the well-being of the businesses. Previous studies on corporate governance and firm performance show very little empirical evidence done in determining the role of human governance. The term human governance itself especially from the Western perspective is still unclearly defined. Thus, the objectives of this study are twofold. First, to investigate the characteristics of human governance from Western and Islamic perspectives. Second, to examine the factors that can improve the quality of human governance in order to mitigate the misconduct behaviour among the employees and the top management. The findings show that Western human governance emphasizes more on the good ethical values of human behaviour but Islamic human governance highlight on religiosity that build good spiritual that generates good behaviour among the Muslim people